Job quality of HE graduates: A comparison across Southern European countries - Suleman, F.; Suleman, A.; Figueiredo, M. C. T. (Society for Research into Higher Education (SRHE), 2021)
Employability skills enables young people to access jobs, while the employment conditions show the differences among skilled workers. This study examines the jobs of young graduates in Greece, Italy, Portugal, and Spain, in their transition into the labour market during economic recession (2011) and recovery (2014, 2017). Empirical analysis draws on EU-LFS data and applies fuzzy clustering to identify common job typologies. We found Precarious, Insecure, and Standard-like jobs. The former involves involuntarily short time flexible, temporary agency and part-time jobs, low wages, and graduates fear job termination. The Insecure cluster comprises voluntary and involuntary non-permanent full-time but long-term contracts, while Standard-like jobs provides stability, but graduates must do atypical work. The data confirm a convergence towards a non-standard job recovery but the distribution of graduates among job categories varies across countries. In Italy and Spain prevail Precarious jobs, while Insecure and Standard-like predominate in Portugal and Greece.